Long-term exposure to fine particulate matter air pollution and type 2 diabetes mellitus in elderly: A cohort study in Hong Kong. (April 2018) - Qiu, Hong; Schooling, C. Mary; Sun, Shengzhi; Tsang, Hilda; Yang, Yang; Lee, Ruby Siu-yin; Wong, Chit-Ming; Tian, Linwei
Abstract: Background: Evidence for the link between long-term air pollution exposure and occurrence of diabetes is limited and the results are mixed. Objectives: We aimed to assess the association of long-term residential exposure to fine particulate matter (PM2.5 ) with the prevalence and incidence of type 2 diabetes mellitus (DM). Methods: This is a prospective cohort study. We studied 61, 447 participants of the Chinese Elderly Health Services cohort in Hong Kong enrolled 1998–2001 and followed participants without DM at baseline to 31 December 2010 to ascertain the first hospital admissions for type 2 DM. Yearly mean residential PM2.5 exposure was predicted based on satellite data. Logistic regression and time-varying Cox regression model were used to evaluate the prevalence and incidence risk of DM associated with PM2.5 while adjusting for potential individual and neighborhood confounders. Results: There were 61, 447 participants included in the study of prevalent DM, and in 53, 905 participants without DM at baseline we studied incident type 2 DM. Over a mean follow-up of 9.8 years, we ascertained 806 incident cases of type 2 DM. After adjusting for potential confounders, the odds ratio (OR) for every interquartile range (3.2 μg/m 3 ) increase of PM2.5 concentration was 1.06 (95% confidence interval (CI): 1.01–1.11) for prevalent DM, while the corresponding hazard ratio (HR) was 1.15 (95% CI: 1.05–1.25) for incident type 2 DM. Conclusions: Long-term exposure to high levels of PM2.5 may increase the risk of both prevalence and incidence of type 2 diabetes mellitus in Hong Kong elderly population. Highlights: Evidence for the link between long-term air pollution exposure and occurrence of diabetes is not definitive. We conducted a cohort study in Hong Kong, a developed non-Western setting with high levels of diabetes and PM2.5 . We examined the association of long-term exposure to PM2.5 with both prevalence and incidence of type 2 diabetes. Long-term PM2.5 exposure may increase the risk of development of type 2 diabetes in older people.